Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
21
Step-by-step explanation:
We find that s(x) = 4x - 7 + (x + 1)^2. Expanding, we get s(x) = x^2 + 6x - 6. Plugging in x = 3, we have s(3) = 3^2 + 6 x 3 - 6 = 21.
Alternatively, we can compute that f(3) = 5 and g(3) = 16, so s(3) = f(3) + g(3) = 21.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.